Factores maternos y peso al nacer del recién nacido. Distrito de Paras - Ayacucho - Ochante Pablo, Gloria (2019)
The present descriptive-correlational cross-sectional research study was carried out in a sample of 146 mothers and their respective term newborns attended in the health facilities of Paras district, from January to July. of 2017, of a population of 356 (100%) in order to determine the relationship that exists between maternal factors: age, intergenesic period, nutritional status and level of knowledge about pregnancy care with birth weight. The data collection techniques were the documental analysis of the perinatal clinical histories and the interview applied to the mothers; as well as the instruments, the check-in sheet and the interview form. For the statistical analysis, the Chi Square statistical test at 95% confidence level was used. The results reached in the present investigation are: 53,4% of mothers were between 20 and 40 years old, 56,2% a normal intergnic period (2-4 years), 53,4% underweight and 50,7% a level of bad knowledge about care during pregnancy. There is a statistically significant relationship between maternal factors: age, intergenesic period and nutritional status with low birth weight in newborns.